John Marshall Harlan papers - Harlan, John Marshall, 1833-1911.; Harlan, James, 1800-1863.
Correspondence, speeches, writings, legal and financial records, subject files, family papers, and other papers relating to Harlan's career in law, politics, and the judiciary. Documents his position as judge on the U.S. Circuit Court for the Seventh Circuit, his service as associate justice of the U.S. Supreme Court, and other aspects of his legal and judicial career. Also documents his legal practice in Kentucky during the 1870s when he was in partnership with Benjamin Helm Bristow and John E. Newman; Harlan's political activities in Kentucky during 1876 when he supported Bristow's candidacy for the Republican presidential nomination; Harlan's appointment (1877) as a member of the commission to settle the disputed state election in Louisiana; his Civil War service with the 10th Kentucky Volunteer Infantry; his role in the Bering Sea arbitration (1892-1893); and his tenure as professor of law at George Washington University Law School.
Includes letters, 1867-1877, from Bristow, especially significant for information concerning the administration of Ulysses S. Grant; published copies (9 volumes) of Harlan's Supreme Court opinions, compiled by Richard D. Harlan; and correspondence, financial and legal records, and other papers of Harlan's father, James Harlan, relating to political affairs.
Family correspondence is with Harlan's wife, Malvina Shanklin Harlan; his sons, James Shanklin Harlan, John Maynard Harlan, and Richard D. Harlan; and his brother-in-law, James G. Hatchitt. Other correspondents include James Gillespie Blaine, J.B. Bowman, Henry Clay, John J. Crittenden, David Davis, George C. Drane, John William Finnell, William Cassius Goodloe, Walter Quintin Gresham, Benjamin Harrison, Rutherford Birchard Hayes, John Rodman, Alexander H.H. Stuart, Augustus Everett Willson, and Bluford Wilson.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Includes photocopies collected from various repositories.
Library of Congress Prints and Photographs Division.
Associate justice of the U.S. Supreme Court, and lawyer and politician of Kentucky.
Collection material in English.
Keywords: Blaine, James Gillespie, -- 1830-1893 -- Correspondence; Bowman, J. B. -- Correspondence; Bristow, Benjamin Helm, -- 1832-1896.; Bristow, Benjamin Helm, -- 1832-1896 -- Correspondence; Clay, Henry, -- 1777-1852 -- Correspondence; Crittenden, John J. -- 1787-1863 -- Correspondence; Davis, David, -- 1815-1886 -- Correspondence; Drane, George C. -- Correspondence; Finnell, John William, -- 1821-1888 -- Correspondence; Goodloe, William Cassius, -- 1841-1889 -- Correspondence; Grant, Ulysses S. -- 1822-1885.; Gresham, Walter Quintin, -- 1832-1895 -- Correspondence; Harlan, James Shanklin, -- 1861-1927 -- Correspondence; Harlan, John Maynard, -- 1864-1934 -- Correspondence; Harlan, Malvina Shanklin, -- 1838-1916 -- Correspondence; Harlan, Richard D. -- Correspondence; Harrison, Benjamin, -- 1833-1901 -- Correspondence; Hatchitt, James G. -- Correspondence; Hayes, Rutherford Birchard, -- 1822-1893 -- Correspondence; Newman, John E., -- 1819-1873.; Rodman, John, -- 1820-1886 -- Correspondence; Stuart, Alexander H. H. -- 1807-1891 -- Correspondence; Willson, Augustus Everett, -- 1846-1931 -- Correspondence; Wilson, Bluford, -- -1909 -- Correspondence; Harlan family; United States. -- Army. -- Kentucky Infantry Regiment, 10th (1861-1864); United States. -- Circuit Court (7th Circuit); United States. -- Supreme Court; George Washington University. -- Law School; Republican Party (U.S. : 1854- ); Bering Sea controversy; Constitutional law -- United States; Elections -- Louisiana -- 1877.; Elections -- United States -- 1876.; Law -- Study and teaching; Law -- United States; Practice of law -- Kentucky; Presidents -- United States -- Election -- 1876.; Sealing -- Law and legislation; Kentucky -- History -- Civil War, 1861-1865.; Kentucky -- Politics and government; Kentucky -- Social life and customs; Louisiana -- Politics and government -- 1865-1950.; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 1869-1877.; United States -- Politics and government -- 19th century; Jurists; Lawyers; Politicians